2010
DOI: 10.2214/ajr.09.2979
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Radiofrequency Ablation for Hepatic Tumors Abutting the Diaphragm: Clinical Assessment of the Heat-Sink Effect of Artificial Ascites

Abstract: Artificial ascites did not show a heat-sink effect on the volume of the ablation zone after percutaneous RFA for the treatment of a hepatic tumor abutting the diaphragm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
14
1
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 27 publications
5
14
1
1
Order By: Relevance
“…The mean volume of 47.8 cm 3 and 38.1 cm 3 in the perdiaphragmatic versus non-peridiaphragmatic groups, respectively, is comparable to previous literature [38]. The lack of significant difference in minor complications agrees with Nam et al [38].…”
Section: Ablation Zone Volume and Complicationssupporting
confidence: 89%
See 3 more Smart Citations
“…The mean volume of 47.8 cm 3 and 38.1 cm 3 in the perdiaphragmatic versus non-peridiaphragmatic groups, respectively, is comparable to previous literature [38]. The lack of significant difference in minor complications agrees with Nam et al [38].…”
Section: Ablation Zone Volume and Complicationssupporting
confidence: 89%
“…Our recurrence rates are similar to Head, et al [7], but increased compared to Nam, et al [38]. But similar to our study, they demonstrated no statistical difference in recurrence rates between the two groups.…”
Section: Therapeutic Efficacy and Assessment Of Recurrencesupporting
confidence: 89%
See 2 more Smart Citations
“…Demostraron que no existían diferencias estadísticamente significativas en los tres grupos en cuanto al tamaño del área de la ablación (210,4774,3, 158,3778,8, 133749,7 mm 2 respectivamente; p¼ 0,188) 28 . En otro reciente estudio realizado en 28 pacientes donde se compara el volumen de ablación y la progresión local del tumor en pacientes tratados mediante RFp con ascitis y RFp convencional, se concluye que no existen diferencias estadísticamente significativas ni en cuanto al volumen del tumor tratado (p ¼0,871) ni en la progresión local del mismo (p ¼ 0,83) 29 .…”
Section: Discussionunclassified